Land Defense System Readiness of Indonesia New Capital City - Panggabean, Jeffri Urbanus; Saputro, Guntur Eko (The Republic of Indonesia Defense University, 2024)
The relocation of Indonesia's capital to East Kalimantan introduces unique security risks distinct from those in Jakarta, including potential vulnerabilities to terrorism, espionage, and internal conflicts due to its remote location. This strategic move aims to address Jakarta’s long-standing issues of traffic congestion, air pollution, flooding, and overpopulation, which have overburdened its infrastructure. However, the development in East Kalimantan also poses environmental challenges, such as threats to tropical forests and endangered species habitats. This study examines the security implications and infrastructure requirements of relocating the capital. Employing a literature study method, it analyzes data from books, academic journals, articles, and other published works to develop a comprehensive foundation for policy formulation. The findings reveal that the relocation requires extensive investments in new defense infrastructure, logistical adjustments, and military operations to ensure national security. Integrating modern defense technology will involve significant investment in infrastructure, research and development, and personnel training. Key priorities include safeguarding radio and satellite communications, constructing a new command center, and incorporating advanced technologies such as drones, radar systems, and cybersecurity measures. Additionally, a data center is essential for big data analysis to enhance intelligence and decision-making capabilities. The relocation also necessitates upgrading military facilities and equipment, conducting comprehensive assessments of existing infrastructure, and ensuring readiness to respond to potential social unrest or conflicts. Despite challenges, relocating the capital provides an opportunity to design a modern and integrated defense system while building sustainable infrastructure. It also strengthens national defense readiness and resilience to address future security threats effectively. This study concludes that careful planning and strategic investments are essential to ensure a smooth transition and secure the new capital, optimizing its strategic advantages while mitigating risks.